2013
DOI: 10.1111/j.1532-950x.2013.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Maintenance of Arytenoid Cartilage Abduction and Stability During Exercise After Laryngoplasty in 33 Horses

Abstract: Limited abductory loss occurs after 6 weeks postoperatively. Resting ACA grade was not a useful predictor of ACS during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…The observed axial collapse may also reflect abnormal biomechanical properties of the elastic cartilage of the corniculate process that is potentially exacerbated by point fixation following LP. In our population, a greater degree of arytenoid cartilage abduction post LP was not associated with an increased risk of dysphagia or reflux, supporting the findings of one study [23] and contradicting others [18,28]. Horses that developed additional forms of DUAO could not be predicted by their post operative abduction grade at rest and we were not able to demonstrate that, exercising LRQ and LRR were lower in these horses compared with horses without additional DUAOs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The observed axial collapse may also reflect abnormal biomechanical properties of the elastic cartilage of the corniculate process that is potentially exacerbated by point fixation following LP. In our population, a greater degree of arytenoid cartilage abduction post LP was not associated with an increased risk of dysphagia or reflux, supporting the findings of one study [23] and contradicting others [18,28]. Horses that developed additional forms of DUAO could not be predicted by their post operative abduction grade at rest and we were not able to demonstrate that, exercising LRQ and LRR were lower in these horses compared with horses without additional DUAOs.…”
Section: Discussionsupporting
confidence: 64%
“…The significant predictive relationship between the degree of post operative left arytenoid cartilage abduction at rest and during exercise using subjective and objective data, contradicts 2 studies that reported no relationship between the grade of post operative abduction at rest and the likelihood of ACC during exercise, except in horses with grade 5 post operative abduction [5,23]. The lack of association between rest and exercise in both of these previous studies may reflect their mixed-breed study populations and the variable exercise intensities performed, compared with the semi-standardised exercise tests performed on Thoroughbred racehorses in the current study.…”
Section: Discussionmentioning
confidence: 85%
“…However, not all horses are able to uphold tracheal protection after airway surgery. Clinical signs may arise immediately after laryngoplasty or may not develop until months or years after laryngoplasty or arytenoidectomy—some horses will cough immediately postoperatively, most commonly horses with Dixon grade 1 or 2 laryngoplasty . The grade of arytenoid abduction at the time of laryngoplasty drops 1 to 2 grades in the first 6 weeks after surgery, which may explain why most horses do not continue to be dysphagic or aspirate .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the penetration of the upper airway is due to failure of protection of the rima glottidis by one or more of (1) failure of midline adduction of both arytenoid cartilages and vocal folds, (2) failure of retroversion of the epiglottis to contact the corniculate processes and vocal folds, and (3) closure of the lateral food channel by the aryepiglottic folds . Our theory is that surgical abduction and stabilization or removal of arytenoid cartilages, vocal folds, and/or aryepiglottic folds may interfere directly with the first and/or third mechanism of airway protection . In addition, laryngeal surgery, by restricting laryngeal elevation by postoperative scarring, interferes with proper epiglottic retroversion and, thus, its role in the protection of the rima glottidis.…”
Section: Introductionmentioning
confidence: 92%
“…5,6 Many minor modifications, including the number and type of sutures inserted and the anchoring process used to minimize loss of abduction, have been described. [1][2][3][4][6][7][8][9][10][11][12][13][14] The degree of abduction that should be targeted during surgery and the consequences of suboptimal abduction on airway mechanics, turbulence, and wall pressure have recently been determined using computer modeling. 15 The earliest description of laryngoplasty also reported performing unilateral ventriculectomy with laryngoplasty.…”
mentioning
confidence: 99%